Cryo-electron Microscopy as a Functional Instrument for Systems Biology, Structural Analysis and Experimental Manipulations with Living Cells. A Comprehensive Analytical Review of the Current Works - Gradov, Oleg V.; Gradova, Margarita A. (Problems of Cryobiology and Cryomedicine, 2014)
The aim of this paper is to give an introductory review of the cryo-electron microscopy as a complex data source for most of the system biology branches, including the most perspective non-local approaches known as localomics and dynamomics. A brief summary of various cryo-electron microscopy methods and corresponding system biological approaches is given in the text. The above classification can be considered as a useful framework for the primary comprehensions about cryo-electron microscopy aims and instrumental tools. We do not discuss any of these concepts in details, but merely point out that their methodological complexity follows only from the structure-functional complexity of biological systems which are investigated in this manner. We also postulate that one can employ some of the cryo-electron microscopic techniques not only for observation, but also for modification and structural refunctionalization of some biological and similar soft matter objects and microscopic samples. In other worlds, we start with the cryoelectron microscopy as a tool for the system biology and progress to its applying as an instrument for system biology and functional biomimetics. All these conclusions can be deduced from the most recent works of the latest years. Probl Cryobiol Cryomed 2014; 24(3):193-211.